30 s sit-to-stand power is positively associated with chest muscle thickness in COVID-19 survivors. (8th July 2022) - Núñez-Cortés, Rodrigo; Cruz-Montecinos, Carlos; Martinez-Arnau, Francisco; Torres-Castro, Rodrigo; Zamora-Risco, Esteban; Pérez-Alenda, Sofía; Andersen, Lars L.; Calatayud, Joaquín; Arana, Estanislao
Introduction: After hospitalization, early detection of musculoskeletal sequelae might help healthcare professionals to improve and individualize treatment, accelerating recovery after COVID-19. The objective was to determine the association between the 30s sit-to-stand muscle power (30s-STS) and cross-sectional area of the chest muscles (pectoralis) in COVID-19 survivors. Method: This cross-sectional study collected routine data from COVID-19 survivors one month after hospitalization: 1) a chest computed tomography (CT) scan and 2) a functional capacity test (30s-STS). The pectoralis muscle area (PMA) was measured from axial CT images. For each gender, patients were categorized into tertiles based on PMA. The 30s-STS was performed to determine the leg extension power. The allometric and relative STS power were calculated as absolute 30s-STS power normalized to height squared and body mass. The two-way ANOVA was used to compare the gender-stratified tertiles of 30s-STS power variants. Results: Fifty-eight COVID-19 survivors were included (mean age 61.2 ± 12.9 years, 30/28 (51.7%/48.3%) men/women). The two-way ANOVA showed significant differences between the PMA tertiles in absolute STS power ( p = .002) and allometric STS power ( p = .001). There were no significant gender x PMA tertile interactions (all variables p > .05). The high tertile of PMA showed a higher allometric STS power compared to the low and middle tertile, p = .002 and p = .004, respectively. Absolute STS power and allometric STS power had a moderate correlation with the PMA, r = 0.519 ( p < .001) and r = 0.458 ( p < .001) respectively. Conclusion: The 30s-STS power is associated with pectoralis muscle thickness in both male and female COVID-19 survivors. Thus, this test may indicate global muscle-wasting and may be used as a screening tool for lower extremity functional capacity in the early stages of rehabilitation planning in COVID-19 survivors.